2019
DOI: 10.1016/j.ijrobp.2019.02.002
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes After Reduced-Dose Intensity Modulated Radiation Therapy for Gastric Mucosa-Associated Lymphoid Tissue (MALT) Lymphoma

Abstract: Purpose/Objectives: In patients with gastric extranodal marginal zone lymphoma of mucosaassociated lymphoid tissue lymphoma (MALT lymphoma), the standard radiation therapy (RT) dose is ≥ 30 Gy. We report the outcome of patients treated with reduced 24 Gy compared with ≥ 30 Gy. Materials/Methods: We reviewed 32 patients diagnosed between 2007 and 2017 with gastric MALT lymphoma and treated with involved site radiation therapy (ISRT) using intensity modulated radiation therapy (IMRT). Response to therapy was bas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
40
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(42 citation statements)
references
References 35 publications
1
40
0
Order By: Relevance
“…With this approach doses to organs at risk were low. This technique has been used at our institution and yields excellent local control rates [9]. It is important to recognize however that in the absence of extended fasting times and high-quality daily CT -IGRT, larger PTV margins are likely required.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…With this approach doses to organs at risk were low. This technique has been used at our institution and yields excellent local control rates [9]. It is important to recognize however that in the absence of extended fasting times and high-quality daily CT -IGRT, larger PTV margins are likely required.…”
Section: Discussionmentioning
confidence: 99%
“…A series of 3 -4 breath hold scans are acquired at time of simulation to ensure reproducibility and for internal target volume (ITV) gastric generation. Typically a 1 cm planning target volume (PTV) expansion on the DIBH ITV-stomach is utilized for planning when daily CT is performed for image guidance [9]. https://doi.org/10.1016/j.ctro.2020.05.013 2405-6308/Ó 2020 The Authors.…”
Section: Methodsmentioning
confidence: 99%
“…The results of this study, in which non-gastric MALT lymphoma was treated using a total dose of 30 Gy, are comparable or better than those of previous studies. As 25 Gy is frequently used for orbital MALT lymphoma [ 8 ] and the irradiation dose for gastric MALT lymphoma can be low [ 23 , 25 ], the irradiation dose to the duodenum and rectum may be reduced.…”
Section: Discussionmentioning
confidence: 99%
“…We have found that radiation can improve outcomes for patients with early-stage follicular, 3 nodular lymphocytepredominant Hodgkin, 4 marginal zone, 5 low-risk NK Tcell nasal type, 6 and mantle cell lymphomas. 7 These patients can now be treated with definitive radiation therapy with no systemic therapy.…”
Section: New Indications For Radiation In Additional Entitiesmentioning
confidence: 97%